The identity of Paratrizygia conformis Tonnoir (Diptera, Mycetophilidae), with comments on its systematic position - de Souza Amorim, Dalton; Oliveira, Sarah Siqueira; Mcalister, Erica (Zootaxa, 2011)
Paratrizygia conformis, the type–species of the genus Paratrizygia, from Tasmania, is redescribed from the holotype. The wing venation and male terminalia are illustrated in detail. The question of the monophyly of the genus—which has four additional species in Chile and southern Argentina, and four species in the Atlantic Forest, in Brazil—is addressed. Comments are made on the relationships of the genus in the Azana–group of Sciophilinae. The hypothesis of monophyly of Paratrizygia is retained, as indicated by the presence of modified, elongated spines on a distal fold of tergite 9.